Activation of RhoA, Smad2, c‐Src, PKC‐βII/δ and JNK in atopic dermatitis. (2nd March 2018) - Lu, Jianyun; Yin, Rong; Fu, Zhibing; Lee, Veronica M; Nelson, John Stuart; Tan, Wenbin
Abstract: Atopic dermatitis is a multifactorial skin disease characterised by chronic and relapsing inflammation whose pathogenesis is incompletely understood. We found that the expression of TGFβR1 and the activation of SMAD2, RhoA, JNK, PKC‐βII/δ and c‐Src were upregulated in the infiltrated inflammatory cells, fibroblasts and vasculatures in the dermis and epidermis. In addition, increases in the expression of TGFβR1 and phosphorylation levels of JNK and c‐Src were positively correlated with the inflammatory progression of atopic dermatitis severity.